Primary school children's attitudes toward use of U-Library portal in Malaysia / Siti Aishah Isnin - Isnin, Siti Aishah (2013)
Digital library has widely known among students. The importance of existence of digital library is as a source of information, book, references, etc. Apart from that, digital library also contribute to be one way of digital reading. Instead of visiting library, people can use digital library or library portal as it can save time and more attractive way in reading activity. Reading has to be developed from early childhood especially when children already enter the primary school. U-Library Portal is another alternative by government to ease people in reading activity plus to enhance the use of ICT. U-Library Portal can be used by all range of age and it is good to be used among students. However, among the primary school children, how far that they interested on using digital library? Towards this question, this research is digging out the attitudes among primary school children towards the use of ULibrary Portal provided by National Library of Malaysia. Based on the technology acceptance model (TAM), researcher can identify the primary school children's attitudes by getting level of perceived ease of use and perceived usefulness (how far the U-Library Portal can increase their reading performance), attitudes itself (how far the existence of U-Library Portal is acceptable for them to use) and behavioral aspects (how far they will likely to use it) towards the use of U-Library Portal through a set of questions. A set of questionnaire has been design in purpose of collecting data regarding on the particular attributes. 50 students from Sekolah Kebangsaan Seksyen 7 Shah Alam have been selected to be part of this research. Moreover, this research focuses on the relationship between children's background (gender, internet experiences, ICT devices) with their attitudes. This research is more to descriptive analysis as this study the attitudes among primary school children toward the use of U-Library Portal. At the end of this study, the results from the analysis were provided whereby there is significant between children's gender, internet experiences, and ICT devices, with their attitudes. This research can be improved in future by adding more attributes that can results to have more strong significant and relationship between attributes.